Research versus practice in software engineering: comparison of expert opinions to measured user priorities - Haigh, M. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2009)
This work explores the differences in software quality perceptions between different groups of people involved with the software development process. Three hundred and fifteen respondents ranked each of thirteen generally accepted attributes of software quality on a scale of one to seven according to their perceived importance for the piece of software most vital to that individual’s work. Differences in the priorities assigned to these attributes were explored using a number of different statistical techniques. Results of this research were compared to the results of several existing studies conducted by experts in theory and practice of software engineering. Comparisons between the studies are valuable, because they allow a comparison of observed correlations between desires for different attributes derived in this study with expert opinion on the extent to which these attributes can be realized in conjunction. Досліджуються розбіжності в сприйнятті якості програмного забезпечення різними групами людей, причетними до його розробки і використання. 315 респондентів оцінили у відповідності до своїх пріоритетів 13 широко поширених атрибутів якості програмного забезпечення. Оцінювання проводилося за шкалою від одного до семи у залежності від того, наскільки важливим респондент вважав даний атрибут. Розбіжності в оцінках пріоритетів цих атрибутів досліджувалися з використанням статистичних методів. Проведено порівняння отриманих емпіричних результатів із результатами кількох досліджень, виконаних за участю експертів в області розробки програмного забезпечення, що дозволяє порівняти спостережувані взаємозв’язки між отриманими в даній роботі бажаними атрибутами з оцінками експертів в області, спільній для всіх цих атрибутів. Исследуются отличия в восприятии качества программного обеспечения разными группами людей, занятыми его разработкой и использованием. 315 респондентов оценили в соответствии со своими приоритетами 13 широко используемых атрибутов качества програмного обеспечения. Оценивание проводилось по шкале от одного до семи в зависимости от того, насколько важным респондент ситал данный атрибут. Отличия в оценках приоритетов этих атрибутов исследовались с привлечением статистических методов. Проведено сравнение полученных эмпирических результатов с результатами нескольких исследований, выполненных при участии экспертов в области разработки программного обеспечения, что позволяет сравнить наблюдаемые взаимосвязи между полученными в данной работе желаемыми атрибутами с оценками экспертов в области, общей для всех этих атрибутов.